Is adjuvant chemotherapy necessary for young women with early-stage epithelial ovarian cancer who have undergone fertility-sparing surgery?: a multicenter retrospective analysis - Yoshiki Ikeda; Masato Yoshihara; Nobuhisa Yoshikawa; Akira Yokoi; Satoshi Tamauchi; Kimihiro Nishino; Kaoru Niimi; Hiroaki Kajiyama (BMC Women's Health, 2022)
Abstract Objective In young patients with early-stage epithelial ovarian carcinoma (EOC) who were received fertility-sparing surgery (FSS), the role of adjuvant chemotherapy is unclear. Here, we performed a multicenter study using inverse probability of treatment weighting (IPTW) to explore the effect of chemotherapy on patients’ survival. Methods Between 1987 and 2015, a retrospective study was carried out, including 1183 patients with stage I EOC. Among them, a total of 101 women with stage I EOC who underwent FSS were investigated, including 64 and 37 patients with or without adjuvant chemotherapy, respectively. Oncologic outcomes were compared between the two arms using original and IPTW cohorts. Results During 62.6 months (median) of follow-up, recurrence was noted in 11 (17.2%) women in the chemotherapy arm and 6 (16.2%) patients in the observation arm. In the unweighted cohort, the 5-year overall and recurrence-free survival (OS/RFS) rates of chemotherapy and observation arms were 86.3/80.8 and 90.2/79.8%, respectively. There was no significant difference between the two groups {Log-rank: P = 0.649 (OS)/P = 0.894 (RFS)}. In the IPTW cohort after adjusting for various clinicopathologic covariates, we also failed to identify a difference in RFS/OS between the two groups {RFS (chemotherapy vs. observation), HR: 0.501 (95% CI 0.234–1.072), P = 0.075: OS (chemotherapy vs. observation), HR: 0.939 (95% CI 0.330–2.669), P = 0.905}. Conclusions Even after adjusting clinicopathologic covariates, performing adjuvant chemotherapy may not improve the oncologic outcome in young patients who have undergone FSS.